Evaluation of the Passenger Areas of Underground Subway Stations in Terms of Visual Comfort: The Sample of Kadikoy and Kartal Stations - Aktop Maden, Didem; Avlar, Erkan (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2017)
Nowadays, the rapid urbanization and the transportation problems caused by this, brought up public transportation systems and urban rail systems especially started to be preferred in metropolises. The type with the highest passenger capacity of the urban rail system is subways and the subways are mostly built underground. In this system, urban transportation is executed by underground stations and tunnels that connect different stations. Station structures are transformed into inefficient environments that are not desired to be used because they are difficult to use when user comfort is not provided, and they do not respond to user requirements. Thus, the passengers are adversely affected physically and psychologically. For this reason station constructions must be designed and applied in accordance with the comfort criteria to be used without problems. This study was limited by visual comfort criteria. In the study, Kadikoy and Kartal Stations in Kadikoy-Kaynarca/ Tavsantepe Subway Line, which is the first metro of Istanbul's Anatolian Side, were selected as the sampling stations. First of all, the visual comfort criteria of the underground subway stations are explained by examples in the world, then the visual comfort attributes of the selected subway stations are determined and these features are evaluated according to both the visual comfort criteria and the questionnaire study made by the users in both stations.
Keywords: Visual comfort criteria; subway; rail systems; underground subway stations; Architecture